2021
DOI: 10.1007/s00167-021-06688-4
|View full text |Cite
|
Sign up to set email alerts
|

A single type of varus knee does not exist: morphotyping and gap analysis in varus OA

Abstract: PurposeTo achieve a higher level of satisfaction in patients having undergone Total Knee Arthroplasty (TKA), a more personalized approach has been discussed recently. It can be assumed that a more profound knowledge of bony morphology and ligamentous situation would be beneicial. While CT/MRI can give 3D information on bone morphology, the understanding of the ligamentous situation in diferent lexion angles is still incomplete. In this study, the dynamic gap widths of a large number of varus knees were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 54 publications
3
62
0
Order By: Relevance
“…However wide variations in laxity have been demonstrated in non-arthritic knees [16]. Furthermore, it has been observed for varus-aligned knees, there is greater laxity in the lateral than the medial compartment, and more laxity in flexion than extension [16], although some more recent studies suggest that laxity in flexion may be equal to that in extension [9]. Whilst these subtle variations exist in the literature to defining what is a well-balanced knee, many authors accept some asymmetry between the medial and lateral compartments [9-16, 34, 35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However wide variations in laxity have been demonstrated in non-arthritic knees [16]. Furthermore, it has been observed for varus-aligned knees, there is greater laxity in the lateral than the medial compartment, and more laxity in flexion than extension [16], although some more recent studies suggest that laxity in flexion may be equal to that in extension [9]. Whilst these subtle variations exist in the literature to defining what is a well-balanced knee, many authors accept some asymmetry between the medial and lateral compartments [9-16, 34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…A commonly utilized approach is one that aims for equal laxity in the medial and lateral compartments in full extension, with a slight lateral laxity being acceptable in flexion. This definition is based on the observation that the medial compartment is constrained by the rigid medial soft tissue structures of the knee (superficial and deep medial collateral ligament complex) and is relatively immobile, compared to the lateral compartment that shows a larger amount of femoral rollback and is more lax, particularly in flexion [9][10][11][12][13][14][15][16], similar to that seen in the native knee, and is supported by published literature [17].…”
Section: Introductionmentioning
confidence: 99%
“…Resection of the PCL increases flexion laxity and can create a medial-lateral compartment mismatch if not adjusted appropriately [ 54 ]. Several definitions of balancing have been described, with many accepting some asymmetry between the medial and lateral compartments [ 55 , 56 , 57 , 58 , 59 , 60 ]. It is unclear if native balancing targets should be replicated in prosthetic designs that are cruciate deficient, and the optimal balancing targets for varus and valgus morphotypes in the tibiofemoral compartments remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple authors have shown that a horizontal joint line, which is the alignment target in mechanical alignment, is present only in 20% of patients, and the mean medial proximal tibia angle (MPTA) is 87 degrees instead of 90 degrees [ 14 , 15 , 16 ]. Hazratwala et al showed on more than 4000 pre-operative knees a wide variation in bony knee morphology, which is quantitatively normally distributed [ 17 ].…”
Section: Introductionmentioning
confidence: 99%